Technologies of Internet-manipulation in the politics’ network space - L. H. Ibragimov (Контуры глобальных трансформаций: политика, экономика, право, 2015)
The author examines the technologies of network manipulation, which are used to influence public opinion in the Internet social network «Vkontakte». The article gives comparative analysis of propaganda activities of the groups, that loyal to the regime and antigovernment communities, and provides examples of methods of manipulative influence used in social networks.